A Study on the Solution of the Cauchy-Euler Equations - Marwa O. A. Younis; Fadwa A. M. Madi (African Journal of Advanced Pure and Applied Sciences, 2024)
In this work, we studied the solution of non-homogeneous Cauchy-Euler equations. To find the general solution, we applied the differential transform method to the reduced associated homogenous equation, and to find a particular solution, we applied the differential transform method to non-homogeneous equation. This study showed that this technique is effective for solving the Cauchy-Euler equations and reduced the size of the calculations compared with the usual methods, especially for the higher-order Cauchy-Euler equations.